The Relationship between Religiousity and New Product Adoption: Case Study on Muslim Students in Yogyakarta - M. Yazid Afandi; Imas Hasanah; Novi Indrayani; Shinta Wulan Saputri; Hanifah Sekar Arsyi (Global Review of Islamic Economics and Business, 2022)
This paper aims to fill the knowledge gap by gathering evidence from the fourth largest Muslim country in the world, Indonesia, through an analysis of the effect of consumer religiosity on new product adoption. The research uses a quantitative research method, where the hypothesis testing was carried out using the Structural Equation Modelling-Partial Least Square (SEM-PLS) method. The data used in this study are primary data obtained from questionnaires distributed to the respondents, per the criteria and research needs. The results show that Islam affects  the purchase decision and adoption of new products. Hypothesis H1 examined in this study has supported the assumption that religion has greater control over a new product adoption. This finding is factual that, in Islam, the actions of consumers are ruled by religious tenets. The distinct feature of this study compared with another similar paper is that this study uses an SEM-PLS method and Warp-PLS in analysing the data. On the contrary, the previous research applies Smart-PLS and SPSS methods. More distinctively, the main focus of this study is the Muslim students in Yogyakarta. This is an exploratory study, in which its findings may not be generalised due to the limited number of participants. The findings of this study draw attention to investigating the impact of religiosity among Muslim consumers on new product adoption. It was so appealing for the authors to see the influence of Islam on the purchase decision and adoption of any new products.